Dialektika Islam dalam Budaya Lokal: Pengaruh Aluk Todolo dan Misi Kekristenan terhadap Perkembangan Islam serta Lahirnya Islam Toraja - Tarran, Belo; Siti Nabilah (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2025)
The presence of Islam in Toraja has had a social impact on the life of the Toraja people. Currently, Toraja is known as a very tolerant area and upholds the value of religious differences. The cultural influences that occur in Toraja society are largely influenced by religion and beliefs. There have been at least four social changes caused by religion and beliefs, starting from the arrival of Aluk 777, Aluk Sanda Saratu', Islam and Christianity. Long before Christianity entered and became the majority religion, Islam was first present in Toraja through trade, marriage and missionary routes. However, in its development, Islam faced various challenges and obstacles. This article will review the development of Islam in Toraja and the factors that caused the slowspread of Islam, as well as the emergence of the concept of Toraja Islam.This research uses qualitative methods with a literature approach, direct observation and interviews. Apart from that, this research also applies historical methods which include four stages of work, namely heuristics, source criticism, interpretation, and historiography. To develop theory and draw conclusions, the author will take a cultural historical and anthropological approach. The results of this research show differences with previous articles written by Johan Wahyudi (2019) examining the causes of the stagnation of Islamization in Tana Toraja. The results of the research found three reasons why Islam is not the dominant religion in Toraja society, namely the sentiment of Toraja society towards Islam due to the invasion of Bone troops. to Toraja, chaos caused by the coffee war and zending activities which surpassed Islamic preaching because it was also supported by the Dutch East Indies government. In this article, the author finds six reasons why Islam is not the majority religion in Toraja. First, the influence of the teachings of aluk todolo is very strong. Second, the sentiment of the Toraja people towards Islam due to the invasion of the Bone kingdom in the 17th century. Third, the sentiment of the Torajan people towards Islam due to the coffee war and slave trade. Fourth, the process of cultural acculturation is slow. Fifth, Christianization carried out by the Dutch East Indies government and zending. Sixth, memories of the dark times caused by the DI/TII incident by Kahar Mudzakkar and the Andi Sose incident.